Longitudinal changes in elite swimmers` 200m freestyle pacing - Goss, C. S.; Greenshields, J. T.; Chapman, R. F.; Stager, J. M. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The purpose of this study was to understand the evolving strategies of elite competitors and to characterize longitudinal changes in pacing parameters in the 200 m freestyle at recent international competitions. The top 16 finishers in the 200m freestyle for men and women at 11 Olympic Games or World Championships from 2000-2017 (n=352) were analyzed. Linear regression was used to characterize pacing with 5 different parameters: linear and quadratic parameters for the effect of lap number, differences between predicted and observed time for the first and last laps, and the residual standard error of the estimate summarizing random and systematic deviations from the model. The mean and the 18-year linear trend of final race time and pacing parameters were evaluated using a linear mixed model and non-clinical magnitude-based inferences with standardized thresholds of small, moderate, large, very large, and extremely large effects (0.2, 0.6, 1.2, 2.0 and 4.0, respectively). Optimization plots of final time versus each parameter were created. Data are presented as mean linear trend change (%) ± 90% confidence interval, unless otherwise specified. Men exhibited a very large decrease in final time (-2.27; ± 0.55), with a moderate increase in linear parameter (1.06; ± 1.25) and small decrease in quadratic parameter (-0.1; ± 0.25). Women exhibited an extremely large decrease in final time (-3.10; ± 0.49), with a small increase in linear parameter (0.61; ± 1.05). The first (0.02 ± 0.06) and last lap (-0.07; ± 0.23) parameters both displayed small changes. Optimization plots displayed no clear optimum for each parameter for either sex. The decreases in final time coupled with the apparent changes in pacing parameters suggest that swimmers have not only swum faster times from 2000 to 2017 but seem to have also adopted a "starting fast" strategy, evidenced by the increase in linear parameter over this period. The lack of optima in finishing time versus parameter plots suggests that elite swimmers accomplish elite times with a variety of strategies and that pacing can be optimized for individuals but not populations.